The neurophysiological foundations of mental and motor imagery (Oxford University Press, 2010)
Mental imagery is the ability to form perceptual-like representations of objects or events on the basis of information stored in memory. Motor imagery is often used when the human body is involved, where subjects imagine the body moving or manipulating objects. The use of mental practice, including motor imagery for the rehabilitation of patients with cerebral motor impairments, is one of the most active areas in the field of motor imagery research. Such data provide evidence for imagery as a method in stroke rehabilitation, leading to reliable reconstruction of neural networks and thus to functional recovery. In recent years, our understanding of imagery has advanced greatly thanks to functional imaging studies using, for example, PET and fMRI. There is now ample evidence that a common neural substrate (albeit not identical) underlies mental imagery and visual perception, on the one hand, and motor performance and motor imagery, on the other.